The effect of treated kenaf fiber on HDPE / glass fiber hybrid composite: characterization and mechanical properties / Nur Nadqirah Abd Jamin - Abd Jamin, Nur Nadqirah (2020)
Composites of HDPE/Glass fiber reinforced with treated kenaf fiber have been prepared by melt mixing. The effect of kenaf fiber loading at 5, 10, and 15 % on mechanical and physical properties of composite sample were studied. FTIR Spectra show the removal of hemicellulose and reduction of OH group present in kenaf fiber surface after modification. DSC result indicated better thermal stability of kenaf fiber after surface modification is slightly increased of melting temperature from 25.01°C to 25.04°C and markedly increased in enthalpy from 282.6 J/g to 315.7 J/g compared to unmodified kenaf fiber. There are increase in tensile strength and tensile modulus at optimum loading of 5 % of kenaf fiber due to good bondability and wettability among the matrix and treated filler. Further increase (10 and 15%) kenaf fiber loading have resulted to reduced tensile strength and tensile modulus due to dispersion and agglomeration of filler in polymer matrix. In elongation at break, the neat HDPE is the highest percent elongation at break. However, the percent elongation at break becomes decreased when reinforced with glass fiber which tends to be more brittle or stiff for the composite sample. In further increasing kenaf fiber loading at 10 and 15 %, it shows the decreasing in percent elongation at break due to the poor interfacial adhesion between filler and matrix. From impact strength, it shows the declined trend of HDPE/Glass fiber reinforced with kenaf fiber in increasing amount of kenaf fiber. This result of impact strength is opposite to theory whereas the impact strength decreased as the decreased in percent crystallinity in high filler loading. This is may cause by the formation of voids during compression molding process. Water absorption showed higher percentage as increase amount of kenaf fiber loading due to OH group existed on the filler. However, comparison data of all properties from untreated and treated kenaf fiber at 5% indicating that treated fiber have higher values than untreated fiber.